The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.1016/j.bjorl.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Association between maxillary sinus pathologies and healthy teeth

Abstract: Dental roots in the maxillary sinus are almost twice as likely to be associated with diseased sinuses than normal sinuses. Healthy teeth whose roots are inside the maxillary sinus may induce an inflammatory response in the sinus membrane. It is suspected that dental procedures may exacerbate the condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 39 publications
0
26
0
3
Order By: Relevance
“…The floor of the maxillary sinus extends into the alveolar process between the roots of adjacent teeth, creating elevations and depressions called ''extensions,'' with narrow cortical areas (3). It has been radiographically demonstrated that most of the roots projecting into the maxillary sinus are in fact surrounded by a thin layer of cortical bone, with perforations present in 14-28% of cases.…”
Section: Anatomy and Physiology Of Maxillary Sinusmentioning
confidence: 99%
See 4 more Smart Citations
“…The floor of the maxillary sinus extends into the alveolar process between the roots of adjacent teeth, creating elevations and depressions called ''extensions,'' with narrow cortical areas (3). It has been radiographically demonstrated that most of the roots projecting into the maxillary sinus are in fact surrounded by a thin layer of cortical bone, with perforations present in 14-28% of cases.…”
Section: Anatomy and Physiology Of Maxillary Sinusmentioning
confidence: 99%
“…It has been radiographically demonstrated that most of the roots projecting into the maxillary sinus are in fact surrounded by a thin layer of cortical bone, with perforations present in 14-28% of cases. Under normal conditions, the relationship between the tooth and the floor of the maxillary sinus consists of either a thin layer of compact bone that provides support to the apical periodontal ligament fibers, to which it firmly adheres, or there is a direct relationship with the maxillary sinus mucosa (3). The bony wall, separating the maxillary sinus from teeth roots, varies from full absence, when teeth roots are covered only by mucous membrane, to a wall of 12 mm (4).…”
Section: Anatomy and Physiology Of Maxillary Sinusmentioning
confidence: 99%
See 3 more Smart Citations